2015
DOI: 10.1002/chem.201501461
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Borohydride‐Modified Zr(BH4)4⋅8 NH3: Low‐Temperature Dehydrogenation Yielding Highly Pure Hydrogen

Abstract: Due to its high hydrogen density (14.8 wt %) and low dehydrogenation peak temperature (130 °C), Zr(BH4 )4 ⋅8 NH3 is considered to be one of the most promising hydrogen-storage materials. To further decrease its dehydrogenation temperature and suppress its ammonia release, a strategy of introducing LiBH4 and Mg(BH4 )2 was applied to this system. Zr(BH4 )4 ⋅8 NH3 -4 LiBH4 and Zr(BH4 )4 ⋅8 NH3 -2 Mg(BH4 )2 composites showed main dehydrogenation peaks centered at 81 and 106 °C as well as high hydrogen purities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The peak at ~43 ° is assigned to the stainless steel sample holder. A typical FTIR spectrum of NaBH4 would display vibrational peaks associated with the BH4group in the region of 2410-2200 cm -1 corresponding to the stretching mode of BH4 -, whereas the bending modes of BH4 -are to be found around 1120 cm -1 [19,20].…”
Section: Composition Of the As-synthesized Materialsmentioning
confidence: 99%
“…The peak at ~43 ° is assigned to the stainless steel sample holder. A typical FTIR spectrum of NaBH4 would display vibrational peaks associated with the BH4group in the region of 2410-2200 cm -1 corresponding to the stretching mode of BH4 -, whereas the bending modes of BH4 -are to be found around 1120 cm -1 [19,20].…”
Section: Composition Of the As-synthesized Materialsmentioning
confidence: 99%
“…The use of NH 3 ligands to saturate and immobilize the metal cation with formation of ammine metal borohydrides (AMBs, [M­(NH 3 ) x ]­[BH 4 ] y ) is an effective strategy to improve thermodynamic stability of metal borohydrides. Although AMBs show improvement of dehydrogenation properties and prevention of B 2 H 6 release compared to metal borohydrides, many of these AMBs tend to release ammonia during thermal decomposition. It has been reported that [Li­(NH 3 ) x ]­[BH 4 ] and [Ca­(NH 3 ) x ]­[BH 4 ] 2 ( x = 1, 2, and 4) release a significant amount of ammonia below 300 °C under dynamic situation. ,, The [Mg­(NH 3 ) 2 ]­[BH 4 ] 2 and [Al­(NH 3 ) 6 ]­[BH 4 ] 3 mainly release hydrogen with a certain amount of ammonia detected during decomposition. , Among these AMBs, zinc ammine borohydride, [Zn­(NH 3 ) 2 ]­[BH 4 ] 2 , shows favorable dehydrogenation properties in terms of hydrogen desorption temperature and purity of gas release.…”
Section: Introductionmentioning
confidence: 99%
“…13 Furthermore, recent experiments have mixed various MBAs with MBs or ammonia borane (NH 3 BH 3 ) to tune the H 2 release temperature and purity. 19,20 Looking at the available experimental data for a large number of MBAs, a clear pattern emerges between the Pauling electronegativity χ p of the metal M in M (BH 4 ) x and the material's decomposition temperature. 21 As can be seen in Fig.…”
Section: Introductionmentioning
confidence: 99%